The Inert vs. the Living State of Matter: Extended Criticality, Time Geometry, Anti-Entropy – An Overview - Longo, Giuseppe; Montévil, Maël (Frontiers in Physiology, 2012)
The physical singularity of life phenomena is analyzed by means of comparison with the driving concepts of theories of the inert. We outline conceptual analogies, transferals of methodologies and theoretical instruments between physics and biology, in addition to indicating significant differences and sometimes logical dualities. In order to make biological phenomenalities intelligible, we introduce theoretical extensions to certain physical theories. In this synthetic paper, we summarize and propose a unified conceptual framework for the main conclusions drawn from work spanning a book and several articles, quoted throughout.